Effects of a classical music meditation program on metacognitive awareness and empathy: a simple mediation model informed by Buddhist mindfulness theory - Lee, Joo-Yeon (Frontiers in Psychology, 2026)
BackgroundMeditation- and music-based interventions have been associated with cognitive and socio-emotional benefits. However, empirical research examining how classical music meditation informed by Buddhist mindfulness theory relates to metacognitive awareness and empathy remains limited.ObjectiveThe present study examined whether participation in a classical music meditation program was associated with changes in metacognitive awareness and empathy, and whether metacognitive awareness served as a statistical mediator within a simple mediation framework.MethodsFifty adults participated in an 8-week classical music meditation program integrating structured music listening, reflective practice, and guided mindfulness. Metacognitive awareness and empathy were assessed using standardized self-report measures. Data were analyzed using the PROCESS macro (version 4.2; Model 4) to test a simple mediation model.ResultsParticipants in the meditation group demonstrated greater increases in metacognitive awareness and empathy compared to a comparison group. Mediation analyses indicated that metacognitive awareness accounted for a statistically significant indirect association between participation in the meditation program and empathy.ConclusionThe findings indicate that a Buddhist-inspired classical music meditation program is associated with enhanced metacognitive awareness and empathy, with metacognitive awareness accounting for part of this relationship. These results contribute to research on contemplative practices by clarifying a cognitive pathway through which music-based meditation may relate to socio-emotional functioning.